A modeling framework to quantify the effects of compaction on soil water retention and infiltration - Ngo-Cong, Duc; Antille, Diogenes L.; Th. van Genuchten, Martinus [UNESP]; Nguyen, Hung Q.; Tekeste, Mehari Z.; Baillie, Craig P.; Godwin, Richard J. (Wiley, 2021)
The water retention curve (WRC) of arable soils from the southeastern United States at different levels of compaction (no compaction, and 10 and 20% increases in soil bulk density) was estimated using the van Genuchten–Mualem (VG) model. The VG water retention parameters of the noncompacted soils were obtained first by fitting measured soil hydraulic data. To construct the WRC of the compacted soils, gravimetric values of the permanent wilting point (θgw, 1,500 kPa) and the residual (θgr) water content were assumed to remain unchanged with compaction. The VG parameter α and exponent η after compaction were estimated using two approaches. In Approach 1, α and η were estimated from saturation, the permanent wilting point, and the residual water content. In Approach 2, the value of η was assumed to remain unchanged with compaction, which allowed α to be estimated immediately from the VG equation. Approach 2 was found to give slightly better agreement with measured data than Approach 1. The effect of compaction on the saturated hydraulic conductivity (Ks) was predicted using semitheoretical approaches and the VG-WRC function. HYDRUS-1D was further used to simulate vertical infiltration into a single-layered soil profile to determine the impact of compaction on the infiltration characteristics of the soils used in our analyses. Results showed that a 10–20% increase in soil bulk density, due to compaction, reduced cumulative infiltration (Ic) at time T = Tfinal (steady-state) by 55–82%, and the available water storage capacity by 3–49%, depending upon soil type.